Features of modern circuitry of strain-resistive pressure sensors: fiber-optic pyrometric thermal compensation, optical radiation supply - E. V. Leun; V. К. Sysoev; A. E. Shakhanov; Yu. N. Mishin (Омский научный вестник)
The article discusses the issues of improving strainresistive pressure sensors (PS) for their joint use with modern achievements of fiber optics (FO). The possibilities of implementation and features of FO pyrometric compensation of the temperature error of semiconductor and resistive strain-resistor, optical and/or electrical heating of the strain gage for selfcalibration of the pyrometer, power supply by optical radiation transmitted through a light guide with galvanic isolation of the PS circuit, increased noise reduction and fire and explosion safety are considered. Noise properties of semiconductor and resistive strainresistor are also considered.